2020
DOI: 10.15244/pjoes/111239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Health of an Urban River Combining DPSIR Framework and an Improved Fuzzy Matter-Element Extension Model: a Case Study from the Jinshui River

Abstract: As the key source for freshwater resources, urban rivers are essential for human survival and urban socio-economic development. Recently, the functions of urban rivers have been damaged by increasing human activities. A better understanding of the health state of urban rivers is the basis of sustainable urban planning. To this purpose, this research took the Jinshui River as a research area. An indicator system for urban river health evaluation was first established using the driving force-pressure-stateimpact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The more indicators are not the better, but the selected influencing factors should be representative, play an important role in the evaluation process, and reflect the characteristics of the evaluation object [29]. The establishment of the indicator system is also simplified as much as possible, either by qualitative analysis of the interrelationships among the indicators or by using quantitative methods to select representative indicators to achieve the optimization of the indicator system.…”
Section: Green Investment Risk Evaluation Index Systemmentioning
confidence: 99%
“…The more indicators are not the better, but the selected influencing factors should be representative, play an important role in the evaluation process, and reflect the characteristics of the evaluation object [29]. The establishment of the indicator system is also simplified as much as possible, either by qualitative analysis of the interrelationships among the indicators or by using quantitative methods to select representative indicators to achieve the optimization of the indicator system.…”
Section: Green Investment Risk Evaluation Index Systemmentioning
confidence: 99%
“…In the literature, many topics of research showed the application of the DPSIR model to understand and plan responses for complex problems (Gari et al, 2018). The DPSIR framework was first proposed by the European Environmental Agency (EEA), which is widely used for analyzing environmental problems (Han et al, 2020).…”
Section: Integrated Methodologymentioning
confidence: 99%
“…It includes natural, social, and economic information and reflects the causal relationship between environmental health and a series of human activities at different scales. The DPSIR framework includes five subsystems: driving force, pressures, state, impacts, and responses, which explore the interaction between humans and the environment (Han et al, 2020).…”
Section: Integrated Methodologymentioning
confidence: 99%
See 2 more Smart Citations